Endovascular treatment of patients with intracranial stenosis with moyamoya-type collaterals. (15th March 2011) - Natarajan, Sabareesh K; Karmon, Yuval; Tawk, Rabih G; Hauck, Erik F; Hopkins, L Nelson; Siddiqui, Adnan H; Levy, Elad I
Abstract : Purpose: The authors report the endovascular treatment of intracranial stenosis in six patients with moyamoya-type collaterals. Patients: All patients previously had experienced a stroke or transient ischemic attack. Lesion locations included a unilateral M1-segment lesion in five patients; and ipsilateral internal carotid artery (ICA)-T, M1 and A1 lesions with contralateral supraclinoid ICA stenosis in one patient. Mean M1 stenosis was 77.3±14.3%. Results: Six patients had balloon angioplasty; in one, a Wingspan stent deployed successfully after angioplasty failed to relieve the stenosis. Mean post-treatment stenosis was 41.0±33.0%. In one patient, vessel rupture occurring during angioplasty caused severe disability. Two patients were asymptomatic for 4 years and 6 months, respectively. One asymptomatic patient had severe restenosis re-treated with intracranial stenting. Two patients became symptomatic and had re-treatment at 1 and 2 months, respectively. Conclusion: Endovascular treatment of intracranial stenosis with moyamoya-type collaterals is possible but is associated with high rates of symptomatic restenosis and target-lesion revascularization.